Uji Efektivitas Implementasi Biomassa Pelet EFB dan Cangkang Sawit pada Co-Firing di PLTU Tembilahan - Dimas Erlangga; Haryono Setiyo Huboyo; Ika Bagus Priyambada (Jurnal Serambi Engineering, 2023)
Energy consumption for power generation in Indonesia is highly dependent on fossil energy, which is mostly supplied from coal-fired power plants. Indonesia has the potential of biomass natural resources that are rich in Carbon Neutral fuels and can be an alternative to stone replacement fuels such as palm kernel shell biomass and pelet efb. Biomass effectiveness tests were conducted at PLTU Tembilahan Riau, with test variables of 25% palm kernel shell biomass co-firing and 5% EFB pelet biomass co-firing with a maximum operational load of 7 MW for 6-8 hours. The results of data analysis are done descriptively. The tested palm kernel shell biomass has a calorific value of 4190 kCal/kg and the calorific value of EFB pelets is 4084 kCal/kg. While the coal used in PLTU Tembilahan has a calorific value of 4199 kcal/kg. The emission results produced in the 5% EFB pelet biomass co-firing test process for sulfur dioxide (SO2) was 97.24 mg/Nm3 and Nitrogen Oxide (NOx) was 497.47 mg/Nm3. While the NOx value of co-firing 25% palm kernel shell biomass is 378.2 mg/Nm3 The emission value is still far below the required standard and below the average emission with 100% coal. The electricity production cost of co-firing 25% palm kernel shell biomass and 5% pelet biomass is more economical than the electricity production cost of 100% coal.